Understanding weather and climate of the last 300 years from ships' logbooks. (17th July 2018) - García‐Herrera, Ricardo; Barriopedro, David; Gallego, David; Mellado‐Cano, Javier; Wheeler, Dennis; Wilkinson, Clive
Abstract : Ships' logbooks have been preserved in archives of different European countries. This paper reviews how their records provide reliable information relevant to meteorology and climatology, extending the observational record back to at least the early 18th century. This allows describing weather during historical events, improving the knowledge on hurricanes or unveiling multidecadal variability previously unsuspected, such as the steady enhancement of the Australian monsoon, the high variability of the atmospheric circulation over the Euro‐Atlantic region during the Late Maunder Minimum or the relationship between the Western North Pacific Summer Monsoon and the El Niño—Southern Oscillation. Observations from ships can feed long‐term reanalysis projects and contribute to reduce their uncertainties over the oceans. The extended record of observations also aids the search of analogues before the human fingerprint, thus improving the detection and attribution of climate change. The integration with paleoclimate proxies is a complex task that requires merging heterogeneous records with a wide range of time resolutions, spatial density, and responses to the climate system. However, recent international efforts open the field to new opportunities. Summing up, logbooks are a consistent, but underexploited, source of relevant climatic data that will widen our knowledge of the past climate. This in turn provides a way to better understand present climatic variations and predict future changes. This article is categorized under: Paleoclimates and Current Trends > Modern Climate Change Abstract : Ships' logbooks help to understand climate variability of the last 300 years.